Technological Parameters of Microfiltration in the Production of Micellar Casein Concentrate - Melnikova, Elena I.; Stanislavskaya, Ekaterina B.; Bogdanova, Ekaterina V. (Current Nutrition & Food Science, 2024)
Background: There are many different factors that influence the process of microfiltration, including membrane pore size, pressure, temperature, and membrane origin. Studying the joint influence of technological parameters in order to justify rational modes of microfiltration is relevant. Objective: This research aimed to define the rational technological parameters of microfiltration, which allow to achieve the target parameters of retentate in the process of obtaining micellar casein concentrate. Methods: Standard and modified methods and techniques have been used in the process of experimental research. The mathematical processing was carried out by methods of mathematical statistics according to several trials data at three stage sequence. Results: As a result of experimental investigations, the applicability of ceramic membranes for microfiltration of skim milk has been shown. The rational pore size has been established as 0,1 μm. To obtain the micellar casein concentrate, it is advisably to carry out the microfiltration of skim milk to the mass fraction of dry solids in concentrate (13 ± 3) %, followed by two-phase diafiltration with a double volume of reverse osmosis water. The rational operating conditions, allowing to get the target value of protein fractions correlation, have been established, as described as follows: input pressure as 0,2 – 0,3 MPa, and temperature as 10 – 15°С. Conclusion: The analysis of microfiltration concentrates and permeates composition of raw milk, including vitamins and minerals content, showed both their high nutritional and biological value and the viability of further processing into food ingredients, including the ingredients for the specialized food products.
Keywords: food ingredients